Pemahaman Masyarakat Gampong Lapang Kabupaten Aceh Barat terhadap Qada dan Fidiah Puasa dalam Al-Qur’an - Salman Abdul Muthalib; Furqan Furqan; Oka Ridayani (TAFSE: Journal of Qur'anic Studies, 2022)
Fasting qada (substitute) and fidiah is an obligation for people who do not fast. Terms, causes, and mechanisms for qada and fidiah have been formulated by scholars based on the Qur'an and hadith. To be accepted by Allah, one must understand and practice religious teachings correctly according to the provisions. In reality, it was found that the practice of qada and fidiah fasting in the Gampong Lapang community was different from the formulation of the ulama. This study will look at the Gampong Lapang community's understanding of qada and fidiah in the Koran and the mechanisms for their daily practice. The results of the study show that a small proportion of people have correctly understood qada, fasting, and fidiah according to the explanation of the scholars and the meaning of letters Al-Baqarah 184 and 185. While most of them are mistaken in understanding the meaning and procedures for its implementation. In their understanding, only the elderly and sick people are given relief, the fidiah applies to parents only, and all sick and traveling people may not fast because there is a fidiah. Qada will be doubled if the year has passed. There is also an understanding that only men have to double the number of days that must be Qada if the year has passed.Abstrak: Puasa qada (pengganti) dan fidiah adalah kewajiban bagi orang yang tidak berpuasa. Syarat, sebab dan mekanisme qada dan fidiah telah rumuskan ulama berdasarkan Al-Qur’an, hadis. Seseorang harus memahami dan mengamalkan dengan benar sesuai ketentuan agar praktik ajaran agama diterima Allah. Realita dalam masyarakat, ditemukan praktik puasa qada dan fidiah dalam masyarakat Gampong Lapang berbeda dengan rumusan para ulama. Kajian ini akan melihat pemahaman masyarakat Gampong Lapang terhadap qada dan fidiah dalam Al-Qur'an dan mekanisme pengamalannya sehari-hari. Hasil penelitian menunjukkan bahwa sebagian kecil masyarakat telah memahami qada puasa dan fidiah dengan benar sesuai dengan penjelasan ulama dan makna surat Al-Baqarah 184 dan 185. Sementara sebagian besar keliru dalam memahami makna dan tata cara pelaksanaannya, mereka memahami bahwa hanya orang tua dan orang sakit yang diberikan keringanan, fidiah berlaku untuk orang tua saja, semua orang sakit dan bepergian boleh tidak berpuasa karena ada fidiah. Qada akan berlipat ganda jika tahun telah berlalu, ada juga yang memahami bahwa hanya laki-laki yang harus melipatgandakan jumlah hari yang diqada jika tahun telah berlalu.